2015
DOI: 10.1093/ilar/ilv012
|View full text |Cite
|
Sign up to set email alerts
|

The Altered Schaedler Flora: Continued Applications of a Defined Murine Microbial Community

Abstract: The gastrointestinal (GI) microbiota forms a mutualistic relationship with the host through complex and dynamic interactions. Because of the complexity and interindividual variation of the GI microbiota, investigating how members of the microbiota interact with each other, as well as with the host, is daunting. The altered Schaedler flora (ASF) is a model community of eight microorganisms that was developed by R.P. Orcutt and has been in use since the late 1970s. The eight microorganisms composing the ASF were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(138 citation statements)
references
References 57 publications
5
133
0
Order By: Relevance
“…Post hoc analysis showed that the wet weights of ceca from ASF or ASF/OxF animals were significantly lower than those from the GF and GF/OxF groups. These data are consistent with previous studies that showed that GF and monocolonized mice displayed enlarged ceca, whereas colonization of GF mice with ASF resulted in smaller ceca of similar morphology, compared with ceca from conventional mice (16,40). In keeping with total cecal oxalate levels (Fig.…”
Section: Colonization With O Formigenes and Altered Schaedler Florasupporting
confidence: 93%
See 2 more Smart Citations
“…Post hoc analysis showed that the wet weights of ceca from ASF or ASF/OxF animals were significantly lower than those from the GF and GF/OxF groups. These data are consistent with previous studies that showed that GF and monocolonized mice displayed enlarged ceca, whereas colonization of GF mice with ASF resulted in smaller ceca of similar morphology, compared with ceca from conventional mice (16,40). In keeping with total cecal oxalate levels (Fig.…”
Section: Colonization With O Formigenes and Altered Schaedler Florasupporting
confidence: 93%
“…Germfree rats, for example, show increased absorption of minerals, including calcium (60), and are susceptible to forming calcium oxalate-containing stones in the bladder (61). In contrast, ASF mice have normal-size ceca and normalized intestinal functions (16). It is possible that improved intestinal epithelial integrity in ASF and ASF/OxF mice, compared to GF and GF/OxF animals, resulted in lower net gastrointestinal oxalate absorption, which in turn could explain the lower levels of urinary oxalate excretion in ASF and ASF/OxF animals than in GF and GF/OxF animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is likely due to the devastating dysbiosis that broadspectrum antibiotic treatment causes, which cannot be restored by a single bacterial species. Dramatic cecal enlargement is a phenomenon observed in antibiotic-treated mice, as well as germ-free mice, and is a measure of their intestinal health 119,170 . The re-colonized mice remained enlarged, showing only a mild amelioration in their cecal size (Fig.…”
Section: Treatment With a Lactobacillus Species Ameliorates Despair Bmentioning
confidence: 99%
“…corresponding to the most abundant genuses observed in the mouse and human microbiomes 170,171 . Since the flora is introduced by individual cultures of component bacteria, the Lactobacillus species can be left out, thus resulting in a balanced flora missing a specific component.…”
Section: Considering the Downsides Of This Model The Ideal System Fomentioning
confidence: 99%